The use of extracorporeal membrane oxygenation in HIV-positive patients with severe respiratory failure: a retrospective observational case series. (March 2019) - Collett, Luke W; Simpson, Thomas; Camporota, Luigi; Meadows, Chris IS; Ioannou, Nicholas; Glover, Guy; Kulasegaram, Ranjababu; Barrett, Nicholas A
The objective is to describe the outcomes of patients with human immunodeficiency virus (HIV) infection who received extracorporeal membrane oxygenation (ECMO) for severe respiratory failure (SRF). The design and setting was a single centre retrospective observational case series, from January 2012 to June 2017, at a tertiary university hospital and regional referral centre for ECMO in the United Kingdom. The participants were all patients referred with SRF and HIV infection. The main outcome measure was patient 90-day survival. Twenty-four patients were referred, of whom nine received ECMO. Six out of nine (67%) of patients were alive at 90 days. Median duration of ECMO was 18 days. There were no identified differences between survivors and non-survivors. ECMO can be used successfully in selected patients with HIV and SRF, including those with poor HIV control and high illness severity. HIV status alone should not exclude patients from treatment with extracorporeal therapy.